Journalism in the data age - Tong, Jingrong (London SAGE Publications, 2022)
Journalism today is entwined with the digital. Stories can come from crowdsourcing and content farms. They can incorporate data visualisations and virtual reality. Journalists can find themselves working as self-employed digital entrepreneurs or for tech giants like Google and Facebook.

This book explores the development of journalism in this era of digital tech, and big and open data. It explores the crucial new developments of online journalism, data journalism, computational journalism and entrepreneurial journalism, and what this means for our understanding of journalism as a profession, and as a part of society.

Using a wealth of international case studies, Jingrong Tong explores contemporary issues such as: AI, Automated news, 'robot reporters', and algorithmic accountability. Digital business models, from venture capital to tech start-ups to crowd-funding. Audiences and dissemination in and age of platform capitalism. Questions of censorship, democracy and state control.
Introduction -- The Communication environment in the data age -- The Crises of quality journalism -- Online journalism -- Data journalism -- Algorithms, automation and journalism -- Entrepreneurial journalism -- Understanding the audience -- Journalistic autonomy -- Journalistic legitimacy -- Conclusion.
Includes bibliographical references (pages 173-210) and index (pages 211-222).
Purchased: Golden Books (17 September 2022); Selected at the Manila International Book Fair 2022.
Keywords: Digital communications; Information society; Journalism; Line social networks; Vital communications; Formation society